The anti-right discourse against gender policies in Cuba during 2021 - Vichot-Borrego, Laura (2022)
During the last three years, the anti-right discourse against public policies with a gender perspective has grown in Cuba. The oppositional character of fundamentalism became evident during 2021, the year in which Resolution 198/2021 (Program for Advancement of Women) was approved by presidential decree; 16/21 (Comprehensive Sexuality Education Program) was validated, as resolution of the Ministry of Education; and versions 22 and 23 of the new Family Code will be released. Between May and July 2021, 25 Christian denomination spoke out against these policies. The representations of fundamental ideas in five of these statements were: the interpretation of the Gender Theory as an ideology, the constant reference to sexual minorities to represent the favored groups and the pathologization of sexualities and diverse sexual identities